Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC

Stepwise nucleophilic substitution to access saturated N-heterocyclic carbene haloboranes with boron-methyl bonds - Kundu, Gargi; Pahar, Sanjukta; Tothadi, Srinu; Sen, Sakya S. (Organometallics, 2020)
Compounds of boranes with N-heterocyclic carbenes are known, yet little attention has been paid to NHC compounds of boron bearing methyl and halogen moieties together. The reason can be attributed to the hazardous methyldichloroborane (MeBCl2), which ignites in air. We describe here convenient solution-phase access to SIDipp.MeBCl2 (SIDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) (3) by a salt metathesis reaction of SIDipp.BCl3 (2) with MeLi. Replacement of the chlorine atoms of 3 with stepwise addition of AgOTf led to the formation of SIDipp.MeBCl(OTf) (4) and SIDipp.MeB(OTf)2 (5). In the case of 4, all of the substituents on the boron atom are different. Subsequently, we extended our synthetic approach to the amidinate system and prepared PhC(NtBu)2B(Me)Cl (7) from the reaction of PhC(NtBu)2BCl2 (6) with MeLi.

Six-membered saturated NHC-stabilized borenium cations: isolation of a cationic analogue of borinic acid - Kundu, Gargi; Balayan, Kajal; Tothadi, Srinu; Sen, Sakya S. (Inorganic Chemistry, 2022)
The reaction of six-membered saturated NHC [1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene; henceforth abbreviated as 6-SIDipp] with PhBCl2 yields a Lewis base adduct, 6-SIDipp.PhBCl2 (1), which readily undergoes nucleophilic substitution reaction with AgNO3, leading to the single (2) and double (3) substitution of both chlorides with ONO2 moieties at the boron atom. The reaction of 1 with 1 equiv of AlCl3 resulted in a borenium cation of composition [6-SIDipp.B(Ph)Cl]+ (4) with AlCl4- as the counteranion. Although borenium cations with different substituents on boron have been reported, a structurally characterized phenylchloroborenium cation remains unknown. Similarly, the reaction of 1 with triflic acid provides the first representative of a new class of borenium cations bearing one hydroxyl and one phenyl group on boron (5), a cationic analogue of borinic acid. Ph-BN H Diphenylborinic acid

Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Saturated NHC-stabilized borenium, boronium, hydride-bridged boron cations, and a bora-acyl chloride - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (ORGANOMETALLICS, 2024)
Keywords: activation; BORINIUM; Chemistry